Antifungal Susceptibility Patterns, In Vitro Production of Virulence Factors, and Evaluation of Diagnostic Modalities for the Speciation of Pathogenic Candida from Blood Stream Infections and Vulvovaginal Candidiasis. (7th July 2014) - Tellapragada, Chaitanya; Eshwara, Vandana Kalwaje; Johar, Ruqaiyah; Shaw, Tushar; Malik, Nidhi; Bhat, Parvati V.; Kamath, Asha; Mukhopadhyay, Chiranjay
Abstract : Candida spp. have emerged as successful pathogens in both invasive and mucosal infections. Varied virulence factors and growing resistance to antifungal agents have contributed to their pathogenicity. We studied diagnostic accuracy of HiCrome Candida Differential Agar and Vitek 2 Compact system for identification of Candida spp. in comparison with species-specific PCR on 110 clinical isolates of Candida from blood stream infections (54, 49%) and vulvovaginal candidiasis (56, 51%). C. albicans (61%) was the leading pathogen in VVC, while C. tropicalis (46%) was prominent among BSIs. HiCrome Agar and Vitek 2 Compact had good measures of agreement ( κ ) 0.826 and 0.895, respectively, in comparison with PCR. We also tested these isolates for in vitro production of proteinase, esterase, phospholipases, and biofilms. Proteinase production was more among invasive isolates (P = 0.017 ), while phospholipase production was more among noninvasive isolates (P = 0.001 ). There was an overall increase in the production of virulence factors among non- albicans Candida . Identification of clinical isolates of Candida up to species level either by chromogenic agar or by Vitek 2 Compact system should be routinely done to choose appropriate therapy.